Analisis Komparasi Penerimaan Retribusi Parkir Di Kabupaten Merangin Dan Sarolangun - Karwaty, Lenny (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2017)
This research is entitled Comparative Analysis of Parking Levy Revenue in Merangin and Sarolangun Regency under the guidance of Parmadi SE, ME. The purpose of the study is to determine the amount of Parking Levy Effectiveness, and to determine the amount of Contribution of Parking Levy Revenue in the Formation of Local Levies, in addition also to determine the difference in the Ability of Parking Levy Revenue in the Formation of Local Levies in Merangin and Sarolangun Regency during the period 2009-2013. The data used in this study are data of Local Retribution, Parking Retribution, Local Revenue, which are sourced from BPS Merangin and Sarolangun Regency. Data analysis using t_Test analysis: Two Sample Assuming Equal Variances. The results of this analysis prove that there are differences in the ability of parking levy revenue in the formation of local retribution seen from the amount of contribution for 5 (five) years. Merangin Regency has an average of 4.28 percent and Sarolangun of 0.52 percent, in the calculation of the t-Test difference test there is a difference of 3.76 percent.